Scoping review of non-pharmacological or self-management interventions for perinatal mood and anxiety disorders tested with Hispanic and Latina women - Lantz, Leslie B.; Gregory, Allison A.; Brown, Roy; Bodnar-Deren, Susan M.; Case, Kim A.; Kinser, Patricia A. (Frontiers in Psychiatry, 2025)
IntroductionResearch on ethnic disparities in perinatal mental health disorders among Latina and Hispanic women has yielded mixed findings. This scoping review aims to identify and describe non-pharmacological or self-management interventions for preventing or reducing symptoms of depression, anxiety, and/or stress associated with perinatal mood and anxiety disorders (PMADs) in Hispanic and Latina women.Materials and methodsWe used the Joanna Briggs Institute (JBI) scoping review methodology and conducted literature searches in MEDLINE (OVID), Embase (OVID), Web of Science, CINAHL, and PsycINFO (EBSCO). Terms such as “self-management interventions,” “mindfulness,” “relaxation,” “exercise,” and “mind-body therapies” were tailored to each database. Additionally, we included the titles of specific interventions that arose in the original searches. We included globally inclusive full-text primary studies published in English or Spanish in peer-reviewed journals, without restrictions on publication date. Studies met the inclusion criteria if they evaluated non-pharmacological or self-management interventions, including mind-body complementary therapies for preventing or reducing symptoms such as depression, anxiety, and/or stress associated with PMADs in predominantly Hispanic or Latina pregnant or postpartum samples.ResultsTwelve studies met inclusion criteria, evaluating a non-pharmacological or self-management intervention in predominantly Hispanic or Latina pregnant or postpartum study samples. The twelve studies evaluated four interventions that used principles of cognitive behavioral therapy (CBT), cognitive behavioral stress management (CBSM), mindfulness, or relaxation. In general, most studies found that the intervention was either equally as effective or more effective at reducing depression, anxiety, or stress symptoms or major depressive episodes as the control group. However, due to the use of varied outcome measures and follow-up timelines, additional research employing consistent RCT methodology is recommended. This would allow for a comprehensive systematic review and meta-analysis to be conducted to determine the effectiveness for these populations.DiscussionWe identified studies in which CBT, CBSM, mindfulness, and relaxation interventions were tested with a study population of predominantly Hispanic and Latina perinatal women. Our findings suggest that these non-pharmacological or self-management interventions should receive more research attention given their potential effect on the prevention or reduction of symptoms such as depression, anxiety, and/or stress in Hispanic and Latina perinatal women.